2022
DOI: 10.1039/d1ra08185c
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis and perovskite oxide-based materials: a remedy for a clean and sustainable future

Abstract: Photocatalytic reaction for CO2 reduction in presence of co-catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 322 publications
(207 reference statements)
1
32
0
Order By: Relevance
“…[47] Because of these, it have been a challenging task to synthesize a material with superior qualities accounting to all of the above mentioned requirements. However, promising advances have been already reported for the implementation of metal-organic frameworks (MOFs), [48,49] perovskite oxides, [50,51] doped semiconductors, [52,53] and photo-sensitized materials. [54][55][56] When modeling photocatalytic processes, two main factors need to be considered: (i) the light absorption on the catalyst ChemElectroChem and (ii) the concentration of pollutants.…”
Section: Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[47] Because of these, it have been a challenging task to synthesize a material with superior qualities accounting to all of the above mentioned requirements. However, promising advances have been already reported for the implementation of metal-organic frameworks (MOFs), [48,49] perovskite oxides, [50,51] doped semiconductors, [52,53] and photo-sensitized materials. [54][55][56] When modeling photocatalytic processes, two main factors need to be considered: (i) the light absorption on the catalyst ChemElectroChem and (ii) the concentration of pollutants.…”
Section: Photocatalysismentioning
confidence: 99%
“…Because of these, it have been a challenging task to synthesize a material with superior qualities accounting to all of the above mentioned requirements. However, promising advances have been already reported for the implementation of metal‐organic frameworks (MOFs), [48,49] perovskite oxides, [50,51] doped semiconductors, [52,53] and photo‐sensitized materials [54–56] …”
Section: Introductionmentioning
confidence: 99%
“…The doping of perovskite materials with trivalent rareearth elements or lanthanides can alter their properties. 19,20 Rare earth (RE) element doped perovskites have drawn attention due to their higher ionic, proton, or mixed conductivities. 21,22 The fundamental reason for higher proton (H + ) conductivity compared to O 2− conductivity is the lower proton activation energy (E a ).…”
Section: Introductionmentioning
confidence: 99%
“…The topic of the photocatalytic (PC) decomposition of organic water pollutants continues to be one of the hottest topics. Perovskite materials and ferrites have generated strong research interest in recent decades as they are among the most promising materials for photocatalytic degradation of pollutants as well as hydrogen generation due to their unique properties and the possibility of their controlled customization [ 1 , 2 , 3 , 4 , 5 , 6 ]. It has recently been shown that the combination of perovskite materials with ferrites and an S-type heterojunction made it possible to significantly enhance the photocatalytic properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%